Changing healthcare professionals' non-reflective processes to improve the quality of care. (April 2022) - Potthoff, Sebastian; Kwasnicka, Dominika; Avery, Leah; Finch, Tracy; Gardner, Benjamin; Hankonen, Nelli; Johnston, Derek; Johnston, Marie; Kok, Gerjo; Lally, Phillippa; Maniatopoulos, Gregory; Marques, Marta M.; et al.
Abstract: Rationale: Translating research evidence into clinical practice to improve care involves healthcare professionals adopting new behaviours and changing or stopping their existing behaviours. However, changing healthcare professional behaviour can be difficult, particularly when it involves changing repetitive, ingrained ways of providing care. There is an increasing focus on understanding healthcare professional behaviour in terms of non-reflective processes, such as habits and routines, in addition to the more often studied deliberative processes. Theories of habit and routine provide two complementary lenses for understanding healthcare professional behaviour, although to date, each perspective has only been applied in isolation. Objectives: To combine theories of habit and routine to generate a broader understanding of healthcare professional behaviour and how it might be changed. Methods: Sixteen experts met for a two-day multidisciplinary workshop on how to advance implementation science by developing greater understanding of non-reflective processes. Results: From a psychological perspective 'habit' is understood as a process that maintains ingrained behaviour through a learned link between contextual cues and behaviours that have become associated with those cues. Theories of habit are useful for understanding the individual's role in developing and maintaining specific ways of working. Theories of routine add to this perspective by describing how clinical practices are formed, adapted, reinforced and discontinued in and through interactions with colleagues, systems and organisational procedures. We suggest a selection of theory-based strategies to advance understanding of healthcare professionals' habits and routines and how to change them. Conclusion: Combining theories of habit and routines has the potential to advance implementation science by providing a fuller understanding of the range of factors, operating at multiple levels of analysis, which can impact on the behaviours of healthcare professionals, and so quality of care provision. Highlights: Improving the quality of care involves changing healthcare professional behaviour. Professional behaviour is driven by both reflective and non-reflective processes. Changing non-reflective, habitual, or routine clinical behaviours is difficult. Theory-based strategies can help address non-reflective clinical behaviours. Future directions for research on non-reflective clinical behaviour are provided.